Wahrheit und Katastrophe: Texte zu Adorno - Braunstein, Dirk (transcript, 2018)
Theodor W. Adorno (1903-1969) is considered to have been a significant thinker of his age - and his critical theory is considered to be the central part (not only) of the German history of science. Dirk Braunstein challenges the settlement of Adorno`s critical theory from the perspectives of the cultural industries, science policies and the pseudo-intellectual viewpoint. His research into Adorno's understanding of criticism, law, economy, materialism, diagnosis of the times and society as well as the philosopher's and sociologist's teachings also deal with the question how these teachings could be adequately reflected from a philological viewpoint.